The effects of inspiratory muscle training on diaphragm thickness, respiratory muscle strength, balance, and core stability in professional dancers: A randomized controlled trial - Aksu, H.; Devran, S.; Morkuzu, S.; Bayraktar, B. (European Journal of Sport Science, 2026)
ABSTRACT This study aimed to investigate the effects of progressive resistance IMT on diaphragm muscle thickness, inspiratory muscle strength, balance, and isometric endurance of the hip*back extensor muscles in professional dancers. Thirty-six professional dancers (15 male, 21 female) aged 16-47 years were randomly assigned to either a training group ( n = 18; 7 males, 11 females) or a control group ( n = 18; 8 males, 10 females). Both groups performed IMT for 8 weeks, with the training group using progressive resistance (60% of maximum inspiratory pressure [MIP]) and the control group using minimal resistance (10% of MIP). Diaphragm thickness, respiratory muscle strength (MIP and MEP), balance (Y-balance test), hip and back extensor muscle endurance (Biering-Sorenson test), and the Oswestry Disability Index (ODI) were assessed before and after the intervention. At baseline, there were no significant differences between groups in demographic characteristics, dance experience, or training regimen ( p > 0.05). After 8 weeks of IMT, the training group showed significant improvements in MIP, MEP, diaphragm thickness at total lung capacity (TLC), hip*back extensor muscle endurance, balance, and ODI scores ( p < 0.01). The improvements in the training group were significantly higher than those in the control group for MIP, MEP, TLC, diaphragm thickness ratio (DTR), hip-back extensor muscle endurance, balance, and ODI scores ( p < 0.01). Progressive resistance IMT effectively improves respiratory muscle strength, diaphragm thickness, balance, hip-back extensor muscle endurance, and reduces disability scores in professional dancers. IMT may be a valuable addition to training programs for dancers to enhance performance.